Substituting clean for dirty energy: A bottom-up analysis - Fabian Stöckl; Alexander Zerrahn (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
We fit CES and VES production functions to data from a numerical bottom-up optimization model of electricity supply with clean and dirty inputs. This approach allows for studying high shares of clean energy not observable today and for isolating mechanisms that impact the elasticity of substitution between clean and dirty energy. Central results show that (i) dirty inputs are not essential for production. As long as some energy storage is available, the elasticity of substitution between clean and dirty inputs is above unity; (ii) no single clean technology is indispensable, but a balanced mix facilitates substitution; (iii) substitution is harder for higher shares of clean energy. Finally, we demonstrate how changing availability of generation and storage technologies can be implemented in macroeconomic models.
Keywords: O44; Q42; Q43; Q55; 330; elasticity of substitution; clean and dirty energy; electricity production; decarbonization; green growth